Ethiopia: Infusing Local Perspectives in Internationalization Policy - Tamrat, Wondwosen (International Higher Education, 2023)
With the development of its internationalization policy in 2020, Ethiopia has joined the list of a number of African countries that have such a policy. Aimed at comprehensive internationalization, the document’s goals and components manifest conscious efforts to infuse local perspectives and dimensions in the policy. Implementation will require more effort in terms of addressing past deficiencies, emerging challenges, and the ambitious components of the new policy.